Alat Bukti Tidak Langsung (Circumstantial Evidence) Dalam Perspektif Hukum Acara Pidana - Wicaksana, Satria Ardyrespati; Setyorini, Erny Herlin (LITERATUS, 2024)
A judge in imposing criminal sanctions against a defendant will always use the provisions of Article 183 of the KUHAP as a guide. This provision essentially stipulates that the judge in sentencing must be based on a minimum of 2 (two) valid and convincing pieces of evidence that the defendant has committed a criminal act. In the provisions of Article 184 of the KUHAP, it regulates 5 (five) pieces of evidence, namely: a). Witness Statement; b). Expert Statement; c). Letter; d). Instruction; e). Defendant's statement. However, in the Central Jakarta District Court Decision Number: 777/Pid.B/2016/PN.Jkt.Pst, the judge used circumstantial evidence which is not regulated in the Criminal Procedure Code. In accordance with this description, the researcher is interested in conducting research with the title "Indirect Evidence (Circumstantial Evidence) in the Perspective of Criminal Law" with the formulation of the problem of the Position of indirect evidence (circumstantial evidence) in the perspective of criminal procedural law and the Ratio decidendi of the Decision of the Central Jakarta District Court No. 777/Pid.B/2016/PN.Jkt.Pst regarding circumstantial evidence. This research aims to explain and analyze the position of circumstantial evidence in the perspective of criminal procedural law, as well as explain and analyze the ratio decidendi of the Decision of the Central Jakarta District Court No. 777/Pid.B/2016/PN.Jkt.Pst regarding circumstantial evidence. The research method used is normative with statutory, conceptual and case approaches. The results of this research indicate that circumstantial evidence is not regulated in the KUHAP. The use of indirect evidence (circumstantial evidence) is based on a doctrine that is in fact contrary to the KUHAP and the principles of criminal law and has a big risk of deviating from the legal aim of realizing legal certainty.